The photophysics of metal halide perovskites for next-generation solar cells - Martin, ES (2019)
Metal halide perovskites have emerged as a promising absorber material for efficient third generation solar cells. In this thesis, the photophysics of these materials are investigated by photoluminescence and optical absorption spectroscopy, focussing on the charge-carrier recombination dynamics and the band gap. The work primarily discusses tin-based perovskite materials, which allow the band gap to be tuned to lower values but currently display poor power conversion efficiencies due to rapid charge-carrier recombination. In addition, the effect of thickness on lead-based perovskites is investigated, allowing the band gap to reach higher values by quantum confinement.